2006
DOI: 10.1038/sj.emboj.7601310
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the unusual structural and functional properties of the variant H2A.Bbd nucleosome

Abstract: The histone variant H2A.Bbd appeared to be associated with active chromatin, but how it functions is unknown. We have dissected the properties of nucleosome containing H2A.Bbd. Atomic force microscopy (AFM) and electron cryo-microscopy (cryo-EM) showed that the H2A.Bbd histone octamer organizes only approximately 130 bp of DNA, suggesting that 10 bp of each end of nucleosomal DNA are released from the octamer. In agreement with this, the entry/exit angle of the nucleosomal DNA ends formed an angle close to 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
117
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(140 citation statements)
references
References 46 publications
23
117
0
Order By: Relevance
“…A recent study of the histone variant H2A.Bbd also suggested that the H4 tail might interact with the H2A pocket in an intranucleosomal manner (49). Nucleosome arrays containing H2A.Bbd exhibited an unusually extended conformation in low salt, suggesting that the DNA was partially unwrapped from the edges of the nucleosome, consistent with studies showing H2A.Bbd nucleosomes protect less than 147 bp of DNA from nuclease digestion (4,14). Moreover, it was found that a restored acidic patch on the H2A.Bbd surface works together with the H4 tail to maintain an intact 29 S (normally extended) chromatin conformation in low salt in which the nucleosomes contain DNA that is fully wrapped around the histone octamers (49).…”
Section: Discussionsupporting
confidence: 58%
“…A recent study of the histone variant H2A.Bbd also suggested that the H4 tail might interact with the H2A pocket in an intranucleosomal manner (49). Nucleosome arrays containing H2A.Bbd exhibited an unusually extended conformation in low salt, suggesting that the DNA was partially unwrapped from the edges of the nucleosome, consistent with studies showing H2A.Bbd nucleosomes protect less than 147 bp of DNA from nuclease digestion (4,14). Moreover, it was found that a restored acidic patch on the H2A.Bbd surface works together with the H4 tail to maintain an intact 29 S (normally extended) chromatin conformation in low salt in which the nucleosomes contain DNA that is fully wrapped around the histone octamers (49).…”
Section: Discussionsupporting
confidence: 58%
“…The H2AL2 nucleosome was quite susceptible to nucleases, suggesting that these nucleosomes have different structural properties, as compared to those of the conventional nucleosome (21). A possible human counterpart of H2AL2, H2A.Bbd, which is highly expressed in the testis, was also suggested to form a specific nucleosome structure with reduced stability (22)(23)(24). Furthermore, nucleosomes containing a testis-specific H2B variant, hTSH2B/TH2B, were reportedly unstable, as compared to the conventional nucleosome (25).…”
Section: Discussionmentioning
confidence: 99%
“…H2A-Bbd is associated with active chromatin. The structure of its central globular domain allows only 130 bp of DNA to be wrapped around the nucleosome, creating a more relaxed, accessible chromatin structure (Doyen et al, 2006b). H2A.Z is associated with both active and inactive chromatin (Cheung and Lau, 2005).…”
Section: Histone Variantsmentioning
confidence: 99%